Rethinking General Education Program for Integrating Local Contexts and English Contents - Editor, Puchong Matchimo; Samarn Ekkapim; Surakan Janghan (Journal of Educational Issues, 2024)
The local and global dimensions are now in balance within the COVID-19 pandemic in all sectors, education needs to be adapted and disrupted for tomorrow. Local contexts in the stream of global movement concerns curriculum and instruction. The local contexts are significant content to promote English by various kinds of contents. This research purposes to study general education program for integrating local contexts and English contents. Target group consisted of teachers who have been taught basic English courses, general education program. The research tools used questionnaire and interviewing form to study the problems and needs for understanding the general education category by integrating content according to local context. As it finding, the local context is the authentic learning experiences that students can learn, they can make a link between local and global dimensions. Conceptual framework is proposed for rethinking genera; education program for integrating local and global English courses, the study needs more discussion how to help students develop learning abilities through the suitable curriculum and instructional practices.